Akuisisi Saham PT Sinar Mitra Sepadan Finance oleh Orix Corporation dari Perspektif UU NO.5 TAHUN 1999 - Ni Putu Elsita Esayana; Ni Luh Mahendrawati; I Wayan Arthanaya (Fakultas Hukum Universitas Warmadewa, 2022)
Acquisition is a form of business strategy that is commonly used in the business world. Acquisition involves the transfer of control over the company being taken over. In the Antimonopoly Law No. 5 of 1999 it is explained that in the acquisition there is an increase in a certain amount that exceeds the existing regulations and is required to notify the KPPU no later than 30 working days from the date of the acquisition which is legally effective. The problems studied in this article are what are the legal consequences of the acquisition of shares of PT Sinar Mitra Sepadan Finance by Orix Corporation on business competition. 5 of 1999. Normative legal research is used in this research by collecting primary, secondary, and tertiary data from legislation, literacy, and electronic media that are related to the topic under study. In the case suffered by Orix Corporation, the imposition of sanctions is considered not to have a strong legal basis which is not in line with the wrongdoing.